Yokohama 2001 : International Triennale of Contemporary Art. - Azumaya, Takashi; Hara, Makiko; Issiki, Yoko; Kohmoto, Shinji; McDonald, Roger; Miyake, Akiko; Muroi, Eri; Nakamura, Nobuo; Nanjo, Fumio; Olson, Scott; Shiner, Eric, C.; Tatehata, Akira; et al. (Yokohama : The Japan Foundation, 2001)
Abdessemed, Adel ; Abramovic, Marina ; Aida Makoto ; Ajiboyé Bamgboyé, Oladélé ; Akasegawa Genpei ; Akimoto Kitsune ; Akita Masami ; Bahc Yiso ; Bigert & Bergström ; Bock, John ; Cai Guo-Qiang ; Candy Factory ; Casagrande & Rintala ; Cattelan, Maurizio ; Choi Jeong Hwa ; Christensen, Jeannette ; Ciona, Joelle ; Claar, Florian ; Deacon, Destiny ; Dean, Tacita ; Ding Yi ; Dodiya, Atul ; Dube, Anita ; Dunér, Karl ; Durham, Jimmie ; Eichhorn, Maria ; Eliasson, Olafur ; Endo Toshikatsu ; Evans, Cerith Wyn ; Fischli & Weiss ; Framis, Alicia ; Fraser, Jacqueline ; Freiij, Peder ; Friedman, Yona ; Fujihata Masaki ; Garaicoa, Carlos ; Gillick, Liam ; Gonzalez-Foerster, Dominique ; Gonzalez-Torres, Felix ; Grigely, Joseph ; Grönlund, Tommi ; Guerrero, Katya ; Ham Kyung ; Heri Dono ; Hjelm, Mats ; Höller, Carsten ; Huang Yong Ping ; Huyghe, Pierre ; Ichihara Hiroko ; Ichiyanagi Toshi ; Ito Zon ; Kac, Eduardo ; Kasahara Emiko ; Kentridge, William ; Koo Jeong-a ; Kusama Yayoi ; Kwon, Sowon ; Liddell, Siobhan ; Masanori, Oda ; Mik, Aernout ; Moriceau, Laurent ; Muraoka Saburo ; Muroi Hisashi ; Nakazawa Ken ; Neudecker, Mariele ; Nguyen-Hatsushiba, Jun ; Nisunen, Petteri ; Oki Keisuke ; Oldendorf, Rainer ; Ono, Yoko ; Orimoto Tatsumi ; Orozco, Gabriel ; Ozawa Tsuyoshi ; Peng Yu ; Pumhösl, Florian ; Ranner, Alexandra ; Rasmus, Knud & Andreasen, Soren ; Rawanchaikul, Navin ; Rhoades, Jason ; de Rijke, Jeroen de & Rooij, Willem ; Rist, Pipilotti ; Sala, Anri ; Sekula, Allan ; Shimabuku ; Shinoda Taro ; Chiharu Shiota ; Slominski, Andreas ; Sone Yutaka ; Stelarc ; Sugimoto Hiroshi ; Sun Yuan ; Tabaimo ; Tan, Fiona ; Téllez, Javier ; Tiravanija, Rirkrit ; Tixier, Laura ; Tomita Toshiaki ; Tomren, Anders ; Tone Yasunao ; Tsubaki Noboru ; Tsuzuki Kyoichi ; Tzaig, Uri ; etc.
biog., tent. p. 375-389
Japans & Engels
Yokohama 2001, International Triënnale of Contemporary Art, Hall Yokohama, September 2 - November 11, 2001
kunstcatalogus